Management of hepatitis B in the era of checkpoint inhibition. Issue 1 (11th February 2020) - Dutcher, Janice
Abstract : Hepatitis B virus (HBV) is a major global health concern, affecting more than 350 million people worldwide. Its management in the setting of cancer treatment can be problematic, particularly with the use of immunological treatment modalities, but also with chemotherapy. Immunological perturbations by chemo or immunotherapy have the potential to permit viral hepatitis reactivation and acute hepatic failure. HBV management algorithms have evolved, based on host tumor factors, viral serological factors, and the specific antitumor agents planned. As new agents enter the antitumor armamentarium, their impact on HBV infection needs to be defined. Zhang et al provide data on the utility of antiviral therapy in the management of HBV antigen positive patients receiving checkpoint inhibitors (CPIs) in preventing hepatitis reactivation, and offers guidance for such management in endemic areas, suggesting that prophylaxis is highly effective in preventing reactivation. This is pertinent to Western cancer therapy also, as a recent study has documented the silent existence of positive hepatitis antigenemia among newly diagnosed cancer patients. Whereas antigen and viral DNA screening is standard of care in Asia and Western Pacific oncology practice, evaluation for latent hepatitis may become a necessary part of management worldwide as CPIs continue to expand their role.